Long non‐coding RNA SNHG6 promotes the growth and invasion of non‐small cell lung cancer by downregulating miR‐101‐3p - Ke Li; Yongxin Jiang; Xudong Xiang; Quan Gong; Chunyan Zhou; Lijuan Zhang; Qianli Ma; Li Zhuang (Thoracic Cancer)
Background The aim of this study was to determine the function of long non‐coding RNA small nucleolar RNA host gene 6 (SNHG6) in non‐small cell lung cancer (NSCLC) and its underlying mechanisms. Methods The association of SNHG6 or miR‐101‐3p with clinicopathological characteristics and prognosis in patents with NSCLC was assessed by TCGA dataset. Cell proliferation and invasion were evaluated by MTT and Transwell assays and SNHG6‐specific binding with miR‐101‐3p was verified by bioinformatic analysis, luciferase gene report and RNA immunoprecipitation assays. qRT‐PCR and Western blot was used to assess the effects of SNHG6 on the expression of miR‐101‐3p and chromodomain Y like (CDYL) in NSCLC cells. A xenograft tumor model in vivo was established to observe the effects of SNHG6 knockdown on tumor growth. Results We found that increased expression of SNHG6 was associated with pathological stage and lymph node infiltration, and acted as an independent prognostic factor of tumor recurrence in patients with NSCLC. Silencing SNHG6 expression repressed cell growth and invasion in vitro and in vivo, but overexpression of SNHG6 reversed these effects. Furthermore, SNHG6 was identified to act as a sponge of miR‐101‐3p, which could reduce cell proliferation and attenuate SNHG6‐induced CDYL expression. Low expression of miR‐101‐3p or high expression of CDYL was related to poor survival in patients with NSCLC. Conclusions Our findings demonstrated that lncRNA SNHG6 contributed to the proliferation and invasion of NSCLC by downregulating miR‐101‐3p.